MODEL PEMBELAJARAN ROPES UNTUK MEREMEDIASI MISKONSEPSI TEKANAN ZAT CAIR SISWA SMP NEGERI 16 PONTIANAK - Ferry Rivaldi; Stepanus Sahala Sitompul; Syukran Mursyid (Universitas Tanjungpura, 2021)
AbstractThe purposed of this research was to determine the effectiveness of remediation misconception by using Review, Overview, Presentation, Exercise, and Summary (ROPES) teaching model to reduce the number of the students who have misconceptions about liquid pressure at SMP Negeri 16 Pontianak. The research method used in this study is a pre-experimental with one group pretest-posttest design. This research used purposive sampling which involved 33 students of VIII A class. The research instrument was a diagnostic test consisting of 9 multiple choice with open reasons. Based on data analysis, there was a decrease percentage the number of the students who have misconceptions with an average 62,19 %. The results of the Mc Nemar test with dk = 1 and α = 5 % showed > which means that the student’s concetual changed significantly after the remediation activity using ROPES model. The ROPES model is effective for reducing the number of students who have misconceptions about liquid pressure with an effect size value of 1,16 which is included in the high category. The ROPES model is expected to be used as alternative remediation activities to reduce the number of students who have misconceptions about liquid pressure.Keywords: Remediation, Misconceptions, ROPES, Liquid Pressure